Methods for SARS-CoV-2 hospital disinfection, in vitro observations - Dora E. Corzo-Leon; Hadeel Mohammed Abbood; Rosa A. Colamarino; Markus F.C. Steiner; Carol Munro; Ian M. Gould; Karolin Hijazi (Elsevier, 2024)
Summary: Introduction: Escalation of chemical disinfection during the COVID-19 pandemic has raised occupational hazard concerns. Alternative and potentially safer methods such as ultraviolet-C (UVC) irradiation and ozone have been proposed, notwithstanding the lack of standardized criteria for their use in the healthcare environment. Aim: Compare the virucidal activity of 70% ethanol, sodium dichloroisocyanurate (NaDCC), chlorhexidine, ozonated water, UVC-222 nm, UVC-254 nm against three SARS-CoV-2 variants of concern cultured in vitro. Methods: Inactivation of three SARS-CoV-2 variants (alpha, beta, gamma) by the following chemical methods was tested: ethanol 70%, NaDCC (100 ppm, 500 ppm, 1000 ppm), chlorhexidine (2%, 1% and 0.5%), ozonated water 7 ppm. For irradiation, a je2Care 222nm UVC Lamp was compared to a Sylvania G15 UV254 nm lamp. Results: Viral inactivation by >3 log was achieved with ethanol, NaDCC and chlorhexidine. The minor virucidal effect of ozonated water was <1 log. Virus treatment with UVC-254 nm reduced viral activity by 1-5 logs with higher inactivation after exposure for 3 minutes compared to 6 seconds. For all three variants, under equivalent conditions, exposure to UVC-222 nm did not achieve time-dependent inactivation as was observed with treatment with UVC-254 nm. Conclusion: The virucidal activity on replication-competent SARS-CoV-2 by conventional chemical methods, including chlorhexidine at concentrations as low as 0.5%, was not matched by UVC irradiation, and to an even lesser extent by ozonated water treatment.